Intergenerational ambivalences new perspectives on parent-child relations in later life - Pillemer, Karl A.; Lüscher, Kurt (Contemporary perspectives on family research, 2004)
This book is an in-depth, cutting-edge report on the intergenerational ambivalence perspective: an innovative framework for understanding parent-adult child relationships that has emerged from work in several disciplines such as sociology, psychology, history, and family therapy in the US and Europe over the past ten years. It is an excellent starting point for anyone interested in the ambivalent feelings experienced between adult children and their parents. With dramatic increases in the life span, many people now have adult relationships with their parents that last 30, 40, or even more years. These intergenerational bonds are perhaps the most stable and enduring ties people experience in our rapidly changing world. At the same time, social norms for how these relationships "should" be conducted have weakened, and many parents and adult children are struggling to understand their roles and responsibilities toward one another. Studying the nature and dynamics of intergenerational ties has now become a key task for social scientists, and a remarkably vigorous area for research. The perspective offered here draws on theory and research that highlight ambivalence as a key organizing concept for the study of intergenerational relations. Rather than focusing on consensus and support on one hand, or conflict on the other, this volume reveals parent-adult child relationships as a complex mix of positive and negative emotions, thoughts and attitudes. This volume's 13 chapters lay out the conceptual and methodological framework for this new perspective, and report on a number of empirical studies. The multidisciplinary group of leading researchers examines core dilemmas facing parents and adult children in the new millennium, the ambivalence such dilemmas create, and how people manage and cope with it.